Determination of active faults by morphotectonic and geophysical data: Karsiyaka (Denizli-Western Anatolia) case - Hancer, Mete; Akyol, Erdal (IJRDO-Journal of Applied Science, 2018)
The graben faults of Aegean Graben system have produced many destructive earthquakes in historical and instrumental periods and the process is still going on. The surface traces of some of these faults, which have formed surface ruptures, may have been lost over time and/or the Holocene aged sediments have been caped. Therefore, difficulties may be encountered in determining the fault lines. This could be vital for microzoning studies in urban areas. In this study, a geological, morphotectonic and geophysical data ware used to identify a buried faulted line in Karsiyaka District of Denizli province. It cannot be observed because of the young sediments on the surface while it can be traced by morphological characteristics in some locations. The fault line has been identified using by geological data, geophysical (resistivity) tools. The results have been verified by trench studies.